Effects of anthropogenic noise as a source of acoustic stress in wild populations of Hippocampus guttulatus in the Ria Formosa, south Portugal - Palma, Jorge (2020)
This study evaluated the effects of underwater noise as a source of acoustic stress in the wild populations of Hippocampus guttulatus in the Ria Formosa, south Portugal. Two different scenarios of underwater noise were tested: transient motor boat sound (63.4-127.6 dB) and constant sound produced by the motor of the boat directly above the animals (up to 137.1 dB). Observations were obtained in the wild between 4 and 10 m depth throughout a 3 min period, using a video camera and a hydrophone set, and compared with a control sample. A significant increase (P < 0.05) in the respiratory rate was observed in 87% of the observed fish. Opercular movements per minute (OMPM) increased from 35.7 +/- 10 (control sample) to 41.2 +/- 15.5 after the first minute, to 45.5 +/- 13.3 after the second (both under transient sound) and to 49.7 +/- 12.5 after the third (under constant sound exposure). Differences in means between the control fish and fish observed during the second (P < 0.01) and third minute of observation (P < 0.0001) were significant. Concordantly, a significant increase (P < 0.05) in the OMPM of fish observed in the first minute and the third minute was noted. In addition to the OMPM increase, 37.5% of the animals abandoned the observation location presumably in an attempt to avoid the negative sound stimuli. The noise caused by boat traffic generated an immediate physiological response, expressed as an increase in OMPM, and a behavioural response resulting in site abandonment, which together can be considered as a negative impact on the seahorse populations. This work contributes to an increasing number of studies that have shown that boat traffic can induce ecological and environmental consequences to aquatic species. Future research should evaluate how navigation exclusion areas could have a positive impact on the seahorse populations inhabiting shallow coastal areas.